The Kotroni Archaeological Research Project (KASP): evaluating ancient Aphidna using multimodal landscape analysis - Agapiou, Athos; Dakouri-Hild, Anastasia; Davis, Stephen; Andrikou, Eleni; Rourk, William (Journal of Greek Archaeology, 2022)
The Kotroni Archaeological Research Project (KASP) seeks to understand the relationship between the natural and human landscape of Aphidna from prehistory through to the present, and how such rural communities contributed to the economic, social and cultural life of larger, ‘core’ centres in the region. As one of the constitutional demes of Classical Athens, Aphidna was steeped in the foundational history of the Athenian polis, which saw in it a primordial, ancestral place tied to myths and legends. It accommodated a Middle Bronze Age cemetery, a Mycenaean/Late Bronze Age citadel, a Classical-Hellenistic fort on the citadel, and a Geometric, Archaic, Hellenistic, and Roman settlement. Furthermore, it was later settled in the form of Byzantine and Frankish monastery estates, Turkish chifliks, Arvanite villages, and the contemporary community of nearby Kapandriti. Being that the area of interest (AOI) is both remarkably well preserved due to construction prohibitions necessitated by the nearby Marathon water reservoir and features a diverse history spanning four millennia, it is an excellent case-study for human landscape inquiry, i.e. understanding diachronic inhabitation and the changing meanings of landscape in the longue durée. Important tasks in this direction include clarifying the spatial extent, chronological framework, and nature of settlement as well as the environmental affordances of the landscape, the combination of which permits a thick description of its cultural history. The main method for this investigation is intensive pedestrian survey. Additional conventional methods include the study of ground historical photographs, conventional maps, older field reports, published scholarship, ancient literature and inscription corpora, traveller accounts (17th-19th century AD), in situ buildings or architectural membra dispersed in the landscape, and artefacts (both those collected during the survey and legacy finds in museum storage, e.g. the National Archaeological Museum). Science-based methods consist of geophysical prospection, geological/geomorphological study, optically stimulated luminescence (OSL) analysis, as well as geospatial informatics focusing on satellite and aerial imagery and Lidar-derived digital terrain models. The results of the intensive survey, the geophysical prospection, and the geological/geomorphological and OSL study are presented elsewhere. In this paper we present the outcomes of remote sensing, arguing that the relevant tools play an important role in the study of human landscapes at all stages of archaeological inquiry (prior, during and after ground truthing), especially when revisiting underexplored areas and employing a multimodal ‘third-wave’ survey methodology. The latter weaves in a multitude of analyses, both conventional and digital, and integrates old and new data.